Recent Advances in Pigeonpea [Cajanus cajan (L.) Millspaugh) Research - Kumar, C. V. Sameer; Singh, I. P.; Patil, Suyash B.; Mula, Myer G.; Kumar, R. Vijay; Saxena, Rachit K.; Varshney, Rajeev K. (International Journal of Economic Plants, 2016)
Pigeonpea or red gram [Cajanus cajan (L.) Millspaugh] is an important food legume of the semi-arid tropics of Asia and Africa. It occupies a prime niche in sustainable farming systems of smallholder rainfed farmers. It occupies a prominent place in Indian rainfed agriculture. It is an integral component in various agro ecologies of the country mainly inter cropped with cereals, pulses, oilseeds and millets. It is the second most important pulse crop next to chickpea. The productivity of pigeonpea has remained low and stagnant over the last few decades thus this prompted scientists to search for novel ways of crop improvement. The level of realized heterosis for seed yield in pigeonpea is comparable to other crops where commercial hybrids have already made a mark in global agriculture. Since the hybrid seed set on the male-sterile plants is chiefly determined by the availability of bee population in the vicinity, pod set is generally poor in the locations with less number of pollinators. Therefore, to harvest good hybrid yields, it is imperative to select suitable seed production sites with good insect pollinator activity.